Fabrication and properties of three-dimensional nanoporous graphene foams with magnesium binder. (15th January 2016) - Zhang, Faming; Li, Ping; Dai, Ge; He, Siyuan
Graphical abstract: Abstract: Three dimensional (3D) nanoporous graphene foams with magnesium as binder were fabricated by spark plasma sintering (SPS) technique. Their microstructures, adsorption properties of nitrogen and mechanical properties were investigated. Experimental results showed that the nanocomposite graphene foams can be fabricated with magnesium binder by the SPS at temperature of 650 °C. The resulting graphene foams exhibited average nanopore size of 5–6 nm and surface area up to (304.4 ± 8) m 2 /g, and high compressive strength up to (4.23 ± 0.09) MPa. Our results demonstrate a facile strategy for the fabrication of 3D nanoporous graphene foams with tailored structure and properties by using the SPS.